Video coding : MPEG standards - Khalifa, Othman Omran; Issa, Sinzobakwira; Siddiqi, Muhammad Umar (IIUM Press, 2011)
Moving Picture Coding Exports Group (MPEG) refers to a whole family of international standards for compression of audio-visual digital data. The most well known are MPEG series which are also formally known as ISO/IEC-13818 and ISO/IEC-14496 [ISO/IEC,2007]. The most important aspects are summarized as follows: The MPEG- I standard was published 1992 with aim of providing VHS quality trough a bandwidth of 1.5 Mb/s, which allowed to playa video in real time from a CD-ROM. The frame rate in MPEG - I is locked at 25(PAL) fps and 30(NTSC) fps respectively. Furthermore, MPEG- I was designed to allow a fast forward and backward search and synchronization of audio and video. A stable behavior, in cases of data loss, as well as allow computation times for encoding and decoding was reached, which is important for symmetric applications, like video telephony